Wild onion (Asphodelus tenuifolius) competition in rainfed chickpea-chickpea cropping system - SIBTAIN,M. (2015)
Chickpea yield potential is limited by weed competition in typical chickpea growing areas of Pakistan where zero tillage crop grown on moisture conserved from rains received during the months of September and August. The objective of this work was to evaluate the growth and yield characteristics of chickpea grown in coexistence with increasing densities of wild onion (Asphodelus tenuifolius). The experiment was comprised of six density levels viz. zero, 20, 40, 80, 160 and 320 plants m-2 of A. tenuifolius. A decrease in chickpea primary and secondary branches per plant, pods per plant, seeds per pod, 100-seed weight and seed yield was observed due to more accumulation of dry matter per increasing densities of A. tenuifolius. The increase in A. tenuifolius density accelerated chickpea yield losses and reached the maximum values of 28, 35, 42, 50, 58 and 96% at 20, 40, 80, 160 and 320 A. tenuifolius plants m-2, respectively. The yield loss estimation model showed that chickpea losses with infinite A. tenuifolius density were 60%. Yield reduction could be predicted by 2.52% with increase of one A. tenuifolius plant m-2. It is concluded that A. tenuifolius has a strong influence on chickpea seed yield and showed a linear response at the range of densities studied.